The future of Pediatric Neurosurgery and ChatGPT: an editor's perspective - Ricardo Santos de Oliveira; Matheus Ballestero (Brazilian Society for Pediatric Neurosurgery, 2023)
The field of pediatric neurosurgery is constantly evolving, and it is difficult to predict the exact future of the field. However, there are some trends and developments that are likely to shape the future of pediatric neurosurgery: -Advancements in technology: Technology is rapidly advancing, and this is likely to have a significant impact on pediatric neurosurgery. For example, robotic-assisted surgery is becoming increasingly common, which can improve precision and reduce the risk of complications. -Gene therapy: Gene therapy is a promising area of research that has the potential to revolutionize the treatment of many neurological disorders. In the future, gene therapy may be used to treat disorders such as brain tumors and epilepsy. -Stem cell therapy: Stem cells have the potential to differentiate into a wide range of cells, including neurons. This makes stem cell therapy a promising area of research for the treatment of neurological disorders. -Minimally invasive procedures: As technology advances, minimally invasive procedures are becoming increasingly common. These procedures typically involve smaller incisions, less scarring, and a faster recovery time. -Precision medicine: Precision medicine is an approach to healthcare that involves tailoring treatment to the specific needs of each patient. In the future, pediatric neurosurgeons may use precision medicine to develop personalized treatment plans for each patient. Overall, the future of pediatric neurosurgery looks promising, with advances in technology, gene therapy, stem cell therapy, minimally invasive procedures, and precision medicine likely to have a significant impact on the field. As the human author of this article, I would like to state that the majority of this article was written by ChatGPT. The use of chatbots and natural language processing (NLP) technology, such as generative pretrained transformer (GPT), has the potential to revolutionize the field of medical writing, albeit with caution.   So, What is ChatGPT? ChatGPT is a type of artificial intelligence (AI) model developed by the company OpenAI and has been designed to generate human-like text. GPT is a type of language model, which means that it has been trained on a large dataset of text and is able to generate new text that is similar to the text it was trained on. It has been particularly successful in the field of NLP, which involves the development of computer systems that are able to understand, interpret, and generate human language (1). Currently, it is important to note that language models such as chatGPT are not yet able to fully replace human medical writers, as they do not have the same level of understanding and expertise in the field of medicine. In addition, the use of language models in medical writing raises ethical concerns, such as the potential for errors or biases in the generated text (2,3). There are factors that still need to be discussed at a deeper level such as ethics in scientific writing, medico-legal factors, accountability, accuracy, and transparency. In addition, the use of any AI tools such as ChatGPT should be transparently declared, similar to the general practice of acknowledging writing assistance in an article or study. These large language models can be a useful aid in scientific writing and editing, especially for non-native English speakers, and can even aid the author in adding accurately formatted references. However, authors should limit the use of these tools to topics that they are subject matter experts on to ensure that the information provided is accurate and up to date. No matter what AI tool is used, the authors remain responsible for the scientific integrity of their publications.